Frederick J. Streng, Emptiness: A Study in Religious Meaning. A Depth Study of the Philosopher Nagarjuna and His Interpretation of Ultimate Reality. Nashville and New York, Abington Press, 1967. 252 pp. - G. C., C. W. Johnson (Estudios de Asia y África, 1968)
-